The Role of Adjuvant Radiotherapy in the Treatment of Papillary Tumors of the Pineal Region: Some General Considerations and a Case Report - Lancia, A; Ingrosso, G; Santoni, R (Klinicka onkologie, 2017)
BACKGROUND: Papillary tumor of the pineal region (PTPR) is a recently defined tumor entity. Its clinical course is characterized by frequent local recurrence, and patients may experience the burden of symptoms due to the anatomical location of the growing mass. Guidelines for treatment protocols, and the role of radiotherapy are still being investigated. CASE: We report the case of a 27-year old woman who was referred to our department after she was diagnosed with PTPR and had undergone multiple surgical interventions. We delivered adjuvant conformal radiotherapy on the gross residual tumor to a total dose of 59.4 Gy (33 × 1.8 Gy). DISCUSSION: After a follow-up period of 41 months, we obtained a complete response to the treatment, according to the Response evaluation criteria in solid tumors criteria (RECIST). Radiation treatment was well tolerated, and the patient did not develop acute and late side effects. The neurological symptoms, which were documented at the diagnosis and after the surgical procedure, have not been recorded at last follow-up. CONCLUSIONS: Formal consensus for managing patients with a diagnosis of PTPR are nonexistent. Despite surgery, this tumor has a tendency to recur. Radiotherapy could have a role in the adjuvant setting and needs to be investigated in a multicenter setting with a long follow-up.Key words: radiotherapy - neurosurgery - magnetic resonance - pineal region - brain tumor.
Keywords: adjuvantní radioterapie; Pineal Gland; Brain Neoplasms; Adult; Neoplasm Recurrence, Local; Radiotherapy, Adjuvant; Pinealoma; Papilloma; lidé; dospělí; Female; ženské pohlaví; epifýza mozková; lokální recidiva nádoru; Humans; pinealom; nádory mozku; papilom